Pelaksanaan Kebijakan Akreditasi PAUD - Irjus Indrawan (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2020)
Early childhood education is a coaching effort for children (0-6 years old) by providing education to grow and develop students’ physical and spiritual, so they are able to step forwards to the next level of education. Having a qualified institution, there should be well-managed and be accredited. Accreditation is crucial for the institutional quality. The qualified institution is greatly expected to creat qualified generation in the future.